LEARNING AGILITY AS A MECHANISM FOR ENHANCING CAREER ADAPTABILITYIN VOCATIONAL EDUCATION - Junaidi, Ahmad; Tuwoso; Marsono; Animatul Chisbiyah , Lismi (Jurnal Ilmiah Didaktika, 2026)
This study investigates the relationships between digital literacy, self-efficacy, and decision-making and career adaptability, with learning agility as a mediating variable among vocational high school students. A quantitative design was employed using structural equation modeling (SEM). The sample comprised vocational students majoring in automotive engineering who had completed fieldwork practice. Data were collected through a Likert-scale questionnaire and analyzed using AMOS. The findings reveal that digital literacy, self-efficacy, and decision-making significantly predict learning agility. However, these variables do not exert a significant direct effect on career adaptability. Learning agility fully mediates the relationships between digital literacy, self-efficacy, decision-making, and career adaptability. This study contributes to the literature by highlighting learning agility as a critical mechanism for enhancing career adaptability in vocational education contexts, emphasizing its role in bridging key individual competencies and adaptive career outcomes.